Legal and Ethical Consideration in Artificial Intelligence in Healthcare: Who Takes Responsibility? - Naik, Nithesh; Hameed, B. M. Zeeshan; Shetty, Dasharathraj K.; Swain, Dishant; Shah, Milap; Paul, Rahul; Aggarwal, Kaivalya; Ibrahim, Sufyan; Patil, Vathsala; Smriti, Komal; Shetty, Suyog; Rai, Bhavan Prasad; et al. (Frontiers in Surgery, 2022)
The legal and ethical issues that confront society due to Artificial Intelligence (AI) include privacy and surveillance, bias or discrimination, and potentially the philosophical challenge is the role of human judgment. Concerns about newer digital technologies becoming a new source of inaccuracy and data breaches have arisen as a result of its use. Mistakes in the high-risk field of healthcare can have devastating consequences for the patient who is the victim of the error. Because patients come into contact with physicians at moments in their lives when they are most vulnerable, it is crucial to remember this. Currently, there are no well-defined regulations in place to address the legal and ethical issues that may arise due to the use of artificial intelligence in healthcare settings. This review attempts to address these pertinent issues highlighting the need for algorithmic transparency, privacy, and protection of all the beneficiaries involved and cybersecurity of associated vulnerabilities.